Profiel van afgestudeerde B.Cur studente van 1997 - S Ballack (AOSIS, 2003)
The purpose of this study is to describe the profile of the B.Cur. graduates who completed their studies in 1997 at the Rand Arikaans University. Theoretical points of departures were used, such as Muller's career management description (Muller, 1998: 353-362) and Northeastern University's five-step model career services (Northeastern University, sa:1).